Land Fever : Dispossession and the Frontier Myth - Marshall, James M., 1924-1989 (Book collections on Project MUSE., 1986)
James Marshall's illuminating study of dispossession on the frontier begins with the autobiography of a pioneer who met repeated failure. Writing in his old age, Omar Morse (1824-1901) loked back on the successive loss of three homesteads in mid-nineteenth century Wisconsin and Minnesota. The frontier as Morse encountered it was a place of runaway land speculation, of high railroad freight rates, of mortgage foreclosures, and of political and economic chaos. Stoic and resilient in adversity, Morse nevertheless expressed the anger of those for whom the Jeffersonian ideal of an independent yeoma.